Evolutionary Evidence of Algal Polysaccharide Degradation Acquisition by Pseudoalteromonas carrageenovora 9T to Adapt to Macroalgal Niches - Gobet, Angélique; Barbeyron, Tristan; Matard-Mann, Maria; Magdelenat, Ghislaine; Vallenet, David; Duchaud, Eric; Michel, Gurvan (Frontiers in Microbiology, 2018)
About half of seaweed biomass is composed of polysaccharides. Most of these complex polymers have a marked polyanionic character. For instance, the red algal cell wall is mainly composed of sulfated galactans, agars and carrageenans, while brown algae contain alginate and fucose-containing sulfated polysaccharides (FCSP) as cell wall polysaccharides. Some marine heterotrophic bacteria have developed abilities to grow on such macroalgal polysaccharides. This is the case of Pseudoalteromonas carrageenovora 9T (ATCC 43555T), a marine gammaproteobacterium isolated in 1955 and which was an early model organism for studying carrageenan catabolism. We present here the genomic analysis of P. carrageenovora. Its genome is composed of two chromosomes and of a large plasmid encompassing 109 protein-coding genes. P. carrageenovora possesses a diverse repertoire of carbohydrate-active enzymes (CAZymes), notably specific for the degradation of macroalgal polysaccharides (laminarin, alginate, FCSP, carrageenans). We confirm these predicted capacities by screening the growth of P. carrageenovora with a large collection of carbohydrates. Most of these CAZyme genes constitute clusters located either in the large chromosome or in the small one. Unexpectedly, all the carrageenan catabolism-related genes are found in the plasmid, suggesting that P. carrageenovora acquired his hallmark capacity for carrageenan degradation by horizontal gene transfer (HGT). Whereas P. carrageenovora is able to use lambda-carrageenan as a sole carbon source, genomic and physiological analyses demonstrate that its catabolic pathway for kappa- and iota-carrageenan is incomplete. This is due to the absence of the recently discovered 3,6-anhydro-D-galactosidase genes (GH127 and GH129 families). A genomic comparison with 52 Pseudoalteromonas strains confirms that carrageenan catabolism has been recently acquired only in a few species. Even though the loci for cellulose biosynthesis and alginate utilization are located on the chromosomes, they were also horizontally acquired. However, these HGTs occurred earlier in the evolution of the Pseudoalteromonas genus, the cellulose- and alginate-related loci being essentially present in one large, late-diverging clade. Altogether, the capacities to degrade cell wall polysaccharides from macroalgae are not ancestral in the Pseudoalteromonas genus. Such catabolism in P. carrageenovora resulted from a succession of HGTs, likely allowing an adaptation to the life on the macroalgal surface.